EVOLUTION DE LA SCOLARITE DES ELEVES PYGMEES DU TERRITOIRE DE WAMBA (RDC) DE 2001 A 2017. Etat des lieux et facteurs conditionnels - Jimmy Lingule Kayomba,; Bolinda wa Bolinda ,; Moïse Aliodri, (IJRDO - Journal of Social Science and Humanities Research, 2019)
The thorny issue of minority emancipation, traditionally supported by different considerations, is related to the respect of human rights, which must apply indiscriminately to the components of the national community. As an eminently politico-administrative issue because related to good governance, it also implies the right to education. Thus, in order to ensure everyone's involvement in its sustainable development, the State must reconcile the emancipation of excluded minorities with their literacy. In this perspective, the educational situation of the Pygmies pupils of Wamba (DRC) and the factors on which it depends, deserve to be declined under this pen to offer a panoramic view of the education of these indigenous peoples in this region.